2019
DOI: 10.1177/2054358119847203
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Weight Before and After Kidney Donation

Abstract: Background: Living kidney donors remain at low risk of end-stage kidney disease (ESKD), but the risk for obese and overweight donors is increased. The Kidney Disease Improving Global Outcomes (KDIGO) clinical guideline recommends that overweight and obese patients pursue weight loss before donation and maintain a healthy post-donation weight. Objective: To determine the trajectory of weight changes before and after living kidney donation. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Our study describes the temporal trends in living kidney donor BMI from initial assessment to two-year postdonation. Although weight gain in the living kidney donor population as a whole has been previously reported by Issa et al [17] and Bugeja et al [18], the main strength of our study is that it clearly demonstrated an initial weight loss from predonation counselling to donation, suggesting that most obese donors are appropriately motivated to lose weight in order to proceed with donation. Although Issa et al [17] report that 12% of obese donors switch to overweight group prior to donation, they do not explain why these trends are observed.…”
Section: Discussionsupporting
confidence: 62%
“…Our study describes the temporal trends in living kidney donor BMI from initial assessment to two-year postdonation. Although weight gain in the living kidney donor population as a whole has been previously reported by Issa et al [17] and Bugeja et al [18], the main strength of our study is that it clearly demonstrated an initial weight loss from predonation counselling to donation, suggesting that most obese donors are appropriately motivated to lose weight in order to proceed with donation. Although Issa et al [17] report that 12% of obese donors switch to overweight group prior to donation, they do not explain why these trends are observed.…”
Section: Discussionsupporting
confidence: 62%
“…Prior data show that overweight and obese donors experience significant weight gain after donation, 33 which is a risk factor for subsequent diabetes and hypertension. 34 The incidence of nonalcoholic fatty liver disease (NAFLD) is increasing, concurrent with rising rates of obesity, hypertension, diabetes, and The impact of various isolated cardiac abnormalities detected on echocardiography or electrocardiogram on long-term outcomes in the donors, if any, is not known. Our survey is the first to document the heterogeneity in practices when these are incidentally found in the otherwise asymptomatic donor candidates.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our survey that significantly fewer programs are considering candidates with BMI >40 now than in the past are in line with these observations regarding the long‐term risks associated with donor obesity. Prior data show that overweight and obese donors experience significant weight gain after donation, 33 which is a risk factor for subsequent diabetes and hypertension 34 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, among all donors, both obese and nonobese, weight significantly increased after kidney donation. 43…”
Section: Discussionmentioning
confidence: 99%